"God is in control": middle-class Pentecostalism and international student migration. Issue 1 (2nd January 2019) - Rocha, Cristina
ABSTRACT: In this article I explore the role of Pentecostalism in the lives of middle-class Brazilian students-turned-migrants in Australia. Brazilian students lead precarious lives in Australia. They are transitioning into adulthood, living away from the homeland and without their families for the first time and they experience downward mobility. In addition, they are at the mercy of constant changes in Australian migration policy. Drawing on three years of multi-sited fieldwork in Australia and Brazil in three Pentecostal churches (the Australian megachurches Hillsong and C3 and a Brazilian church), I argue that Pentecostalism supports these students in their migration pathway. This is particularly the case because these are Seeker churches. By focusing on youth culture, entertainment, and informality and by addressing real-life situations, these churches cater to middle-class sensibilities. I also contend that their religious beliefs and practices are interwoven with the students' narratives of migration to Australia. Thus the students pray for visas, jobs, and sponsorships for permanent residency and they see every obstacle and achievement as God's work in their lives. For them, God determines whether they can stay or must return home. Importantly, citizenship in God's kingdom gives them a more significant sense of belonging than that of the Australian state.